Childhood high-risk acute lymphoblastic leukemia in first remission: results after chemotherapy or transplant from the AIEOP ALL 2000 study. - Conter, Valentino; Valsecchi, Maria Grazia; Parasole, Rosanna; Putti, Maria Caterina; Locatelli, Franco; Barisone, Elena; Lo Nigro, Luca; Santoro, Nicola; Aricò, Maurizio; Ziino, Ottavio; Pession, Andrea; Testi, Anna Maria; et al. (Blood, 2014)
The outcome of high-risk (HR) acute lymphoblastic leukemia patients enrolled in the AIEOP-BFM ALL 2000 study in Italy is described. HR criteria were minimal residual disease (MRD) levels ≥10(-3) at day 78 (MRD-HR), no complete remission (CR) at day 33, t(4;11) translocation, and prednisone poor response (PPR). Treatment (2 years) included protocol I, 3 polychemotherapy blocks, delayed intensification (protocol IIx2 or IIIx3), cranial radiotherapy, and maintenance. A total of 312 HR patients had a 5-year event-free survival (EFS) of 58.9% (standard error [SE] = 2.8) and an overall survival of 68.9% (SE = 2.6). In hierarchical order, EFS was 45.9% (4.4) in 132 MRD-HR patients, 41.2% (11.9) in 17 patients with no CR at day 33, 36.4% (14.5) in 11 patients with t(4;11), and 74.0% (3.6) in 152 HR patients only for PPR. No statistically significant difference was found for disease-free survival in patients with very HR features [MRD-HR, no CR at day 33, t(4;11) translocation], given hematopoietic stem cell transplantation (HSCT) (n = 66) or chemotherapy only (n = 88), after adjusting for waiting time to HSCT (5.7 months). Patients at HR only for PPR have a favorable outcome. MRD-HR is associated with poor outcome despite intensive treatment and/or HSCT and may qualify for innovative therapies. The study was registered at www.clinicaltrials.gov as #NCT00613457.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Combined Modality Therapy; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Neoplasm, Residual; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Radiotherapy; Remission Induction; Treatment Outcome